Analisis Efektivitas Transmisi Kebijakan Moneter Melalui Interest Rate Channel dan Asset Price Channel di Indonesia pada Masa Inflation Targeting Framework (ITF) - Husnansyah, Fadhlil (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of this research is to evaluate the monetary policy transmission more effective between the of interest rate channel with asset price channel on Inflation Targeting Framework (ITF). Variables that included in interest rate channel those are BI Rate, interbank call money, deposits rates, loans interest rate, real consumption, and inflation. Meanwhile, the variables that included in asset price channel, namely BI Rate, interbank call money, composite stock price index (IHSG), real investment, and inflation. Data that used is secondary data which obtained from the official website of Bank Indonesia (BI) and Statistics Indonesia (BPS). This research will use time series data from 2005: Q3 - 2014: Q4. Analysis of used data is the VectorError Correction Model (VECM) with Eviews 6.0 application. The result shows based on test results impulse response (IRF) and variance decomposition (VD) that the overall of asset pricechannel is more effective within the ITF framework compared of interest rate channel. Â Keywords: interest rate channel, asset price channel, inflation targeting, Vector Error CorrectionModel (VECM)